A case of ANA-negative systemic sclerosis treated with methylprednisolone - Rogacion, Carminda P.; Uy, Veronica S,; Ugalde, Reynaldo L.; Vista, Emmerson Gale S. (UI Scholars Hub, 2019)
Background: Systemic sclerosis is a multi-systemic disease characterized by excessive fibrosis, inflammation, and vasculopathy. Common clinical features include skin thickening, telangiectasias, salt and pepper skin, beak-shaped nose, and microstomy. We report a case of ANA-negative systemic sclerosis in a male patient. Case illustration: Our patient presented with a 10-month history of diffuse hyperpigmentation, skin tightening and decreased mouth aperture, accompanied by digital ulcers, hypopigmented macules and violaceous discoloration of the digits upon exposure to cold temperature. Punch biopsy done revealed mild acanthosis of the epidermis with basal cell layer hyperpigmentation, vacuolar alteration and thickening of the basement membrane zone. ANA was negative. Anti-Scl70 was positive. Patient was treated with methylprednisolone which was tapered over a course of 1 month, with noted decrease in tightening of the skin. Digital ulcers and discoloration of digits upon exposure to cold temperature were no longer observed. Discussion: Diagnosis of systemic sclerosis is made on the presence of scleroderma proximal to the metacarpophalangeal joints, with two of the following minor criteria: sclerodactyly, digital ulcerations or bibasilar pulmonary fibrosis, as well as symptoms involving other organ systems; musculoskeletal, gastrointestinal, respiratory, cardiac, and renal. Conclusion: While the presence of certain distinct features are needed in the diagnosis of systemic sclerosis, a distinct subset of the disease may be ANA-negative and may correspond to better prognosis. A thorough physical and diagnostic examination is needed in order to provide the optimum treatment for each patient. This would prevent systemic complications and further progression of the disease.